2009
DOI: 10.4070/kcj.2009.39.5.209
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Aortopulmonary Fistula Caused by a Huge Thoracic Aortic Aneurysm

Abstract: Aortopulmonary fistula is an uncommon but often fatal condition resulting as a late complication of an aortic aneurysm. The most common cause is erosion of a false aneurysm of the descending thoracic aorta into the pulmonary artery, resulting in the development of a left-to-right shunt and leading to acute pulmonary edema and right heart failure. We report an our experience with aortopulmonary fistula as a rare complication associated with thoracic aortic aneurysm and high output heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…An aortic aneurysm is one such complication 5. In rare instances, aortic aneurysm may lead to further complications of fistula formation between the aorta and the pulmonary artery 1 6. In 1924, Boyd reported that the occurrence of aortopulmonary fistula was nearly 4% among the 4000 autopsy cases with thoracic aortic aneurysm investigated in the study 7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An aortic aneurysm is one such complication 5. In rare instances, aortic aneurysm may lead to further complications of fistula formation between the aorta and the pulmonary artery 1 6. In 1924, Boyd reported that the occurrence of aortopulmonary fistula was nearly 4% among the 4000 autopsy cases with thoracic aortic aneurysm investigated in the study 7.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of patients with aortopulmonary fistula remain asymptomatic, when they do occur, symptoms may include chest pain, haemoptysis and dyspnoea 1 6. Further, an aortic aneurysm of more than 6 cm diameter is common in patients with aortopulmonary fistulae and is frequently associated with the development of acute left-to-right shunt, new murmur, systemic arterial hypertension, signs of cardiac insufficiency and severe pulmonary hypertension 1 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the patient had no pre-existing pulmonary disease, surgical history and hemoptysis, an aortopulmonary fistula might have formed due to erosion from the continuous pulsatile friction between the pulmonary artery and the aortic aneurysm wall, or an aortobronchial fistula between the aortic and bronchial lumina was created because of compression of the tracheobronchial tree by the enlargement of the thoracic aneurysm. This may have induced pressure necrosis, which can lead to erosion of both the aortic and bronchial walls 15)16). Endovascular stent graft repair of an aortopulmonary fistula appears to be safe and well tolerated 17)…”
Section: Discussionmentioning
confidence: 99%